Assessment of agronomic traits in fall armyworm (Spodoptera frugiperda) resistant maize (Zea mays) hybrids grown in the derived savanna agro-ecology of Nigeria - Olufemi Stephen Akande; Adesike Oladoyin Olayinka; Moses Adeolu Adebayo (PLoS ONE, 2026)
Maize production in Nigeria has increased in recent years, but fall armyworm infestation remains a major constraint to high productivity, particularly during the minor cropping season. Twenty-six fall armyworm-resistant maize hybrids and six commercial checks were evaluated for grain yield and other traits using an 8 × 4 alpha-lattice design with three replications. Data collected at key growth stages and harvesting were analyzed using R statistical software version 4.4.2. Hybrids exhibited significant (p < 0.05) differences for grain yield, plant aspect, ear aspect, southern corn leaf blight, curvularia leaf spot and foliar fall armyworm damage at 8 and 12 weeks after planting. Notably, five experimental hybrids exhibited superior performance, combining high yield with desirable agronomic traits and low foliar fall armyworm damage. FAWSYN-1/(TZLComp. 1 C6-W-39-1-1)-B-B, followed closely by FAWSYN-1/IITATZI2305, FAWSYN-2/(TZLComp. 1 C6-W-39-1-1)-B-B, FAWSYN-1/TZISTR1121, and FAWSYN-3/IITATZI2305 exhibited the highest superiority indices across environments. When further tested for performance stability across more diverse agro-ecologies, the selected hybrids may be released as maize cultivars to mitigate fall armyworm attacks among Nigerian farmers.